Nursing history management in the intensive pediatric therapy context - Jaynara Menezes Sousa Pinheiro; Francisca Georgina Macedo de Sousa; Andréa Cristina Oliveira Silva; Nicole Maria Costa e Silva; Danilo Marcelo Araújo dos Santos (Universidade Federal de Santa Maria, 2018)
Aim: to characterize the management of Nursing History according to the data filling made by the Pediatric Intensive Care Unit nurses. Methods: retrospective documentary research using 135 Nursing Histories of hospitalized children from January 2015 to January 2016. An instrument built from the items from each Nursing History Block of the research context service was used. The scores ranged from 1 to 189 points and allowed the filling to be classified as Poor (1 - 66 points); Bad (67 - 100 points); Regular (101 - 145 points); Good / Great (145 or more points). Results: from the analyzed Nursing Histories, 47.2% were classified as regular, 23.7% bad, 22.2% great and 6.9% as poor. Conclusions: the management of Nursing History was characterized as incipient, ambivalent, ambiguous, incomplete and disqualified regarding the formality of its filling in the care practices of the intensive care unit nurse.